"El Dean de Canterbury a la fabrica de Vidrio, Badalona". The Dean 2nd from left, Souchy 3rd from right. Copied from CNT collection
"El Dean de Canterbury a la fabrica de Vidrio, Badalona". The Dean 2nd from left, Souchy 3rd from right. Copied from CNT collection.